Extracellular Matrix-Oriented Proteomic Analysis of Periodontal Ligament Under Mechanical Stress - Thant, Lay; Kaku, Masaru; Kakihara, Yoshito; Mizukoshi, Masaru; Kitami, Megumi; Arai, Moe; Kitami, Kohei; Kobayashi, Daiki; Yoshida, Yutaka; Maeda, Takeyasu; Saito, Isao; Uoshima, Katsumi; et al. (Frontiers in Physiology, 2022)
The periodontal ligament (PDL) is a specialized connective tissue that provides structural support to the tooth and is crucial for oral functions. The mechanical properties of the PDL are mainly derived from the tissue-specific composition and structural characteristics of the extracellular matrix (ECM).　The ECM also plays key roles in determining cell fate in the cellular microenvironment thus crucial in the PDL tissue homeostasis. In the present study, we determined the comprehensive ECM profile of mouse molar PDL using laser microdissection and mass spectrometry-based proteomic analysis with ECM-oriented data curation. Additionally, we evaluated changes in the ECM proteome under mechanical loading using a mouse orthodontic tooth movement (OTM) model and analyzed potential regulatory networks using a bioinformatics approach. Proteomic changes were evaluated in reference to the novel second harmonic generation (SHG)-based fiber characterization. Our ECM-oriented proteomics approach succeeded in illustrating the comprehensive ECM profile of the mouse molar PDL. We revealed the presence of type II collagen in PDL, possibly associated with the load-bearing function upon occlusal force. Mechanical loading induced unique architectural changes in collagen fibers along with dynamic compositional changes in the matrisome profile, particularly involving ECM glycoproteins and matrisome-associated proteins. We identified several unique matrisome proteins which responded to the different modes of mechanical loading in PDL. Notably, the proportion of type VI collagen significantly increased under compressive forceat the mesial side, contributing to collagen fibrogenesis. On the other hand, type XII collagen increased under tension force at the PDL-cementum boundary of the distal side. Furthermore, a multifaceted bioinformatics approach illustrated the potential molecular cues, including PDGF signaling, that maintain ECM homeostasis under mechanical loading. Our findings provide fundamental insights into the molecular network underlying ECM homeostasis in PDL, which is vital for clinical diagnosis and development of biomimetic tissue-regeneration strategies.